GAMBARAN PEMERIKSAAN STATUS GIZI BALITA DI POSYANDU SRIKAYA, RANGKAPAN JAYA KOTA DEPOK (STIKes Mitra Keluarga, 2024)
One of the goals of the Sustainable Development Goals (SDGs) is good health and well-being. This goal is an important indicator that a country needs to have a quality next generation. Nutritional factors are the basis for creating quality human resources (HR). Integrated Service Post (Posyandu) activities are one of the pillars in helping to realize improvements in the quality of good health. The purpose of this study was to observe and monitor the role of Posyandu cadres in improving the health status of children, especially toddlers. The implementation of this Community Service activity consists of the preparation, implementation, and evaluation stages. In the preparation stage, the team asked the cadres what activities were carried out at Posyandu Srikaya, RW.18 Rangkapan Jaya Depok. Based on the results of interviews in the preliminary study, the examination activities only included examinations of PB (Body Length) / TB (Body Height) and Body Weight in Toddlers. After obtaining information, the team made technical preparations and prepared Medline Tapes to measure Upper Arm Circumference and Head Circumference in toddlers. In the implementation stage, the team helped with the examination and measurement of toddlers. The number of toddlers present was 18 toddlers out of a total of 23 toddlers in the area. The majority of toddlers already had normal nutritional status, there was a female toddler with obese nutritional status (>3SD). Obese toddlers need attention from local cadres and health workers who make routine visits to the Srikaya Posyandu. PMT has also met the requirements of the Ministry of Health, namely being made from local food ingredients with nutritional content that is suitable for toddlers aged 6-59 months. The PMT given at that time was pumpkin pudding which was also added with eggs and coconut milk in its making as well as fruit satay for vitamin and mineral needs. However, there are still some cadres who have not properly measured their height and upper arm circumference.